Causes of Occupational Changes among Dalit Communities of Kaski District - Palikhe, Amin; Subedi, Netra Prasad; Bhandari, Hari Bahadur; Adhikari, Nabin Bahadur (Janapriya Journal of Interdisciplinary Studies, 2021)
Occupational change from traditionally adopted occupations to new occupations is an increasing trend in the new generation of Nepalese society. And this seems relatively high in the people of Dalit communities. This study aims to investigate the status of occupational change and their causes among the Dalit communities of the Kaski district. This study has conducted by using the quantitative nature of data collected from primary sources with the help of a structured questionnaire. Total 300 head of the household covering 150 from each urban and rural area including 50 each from three Dalit caste groups namely Nepali (Sarki), Pariyar (Damai), and Bishowkarma (Kami) are the sample for this study. The information regarding the occupational change was collected from the head of the household. The study reveals that there is a statistically significant difference in the involvement in a particular occupation in the past and at present. The tendency of abandoning past & caste-based occupation and shifting to new & modern occupation is high (63.33%) among the people of the Dalit communities. While investigating towards causes for occupational change; insufficient for livelihood, low return compares to costs & efforts, lack of skills & knowledge of past occupations, skills & knowledge of other occupations, lack of work for a whole year in traditional occupations, have found as the key causes for the occupational change in the Dalit communities. However, 36.67 percent still involved in past occupations, and the key causes for no change in the past occupations are lack of other skill & knowledge, satisfaction in the past occupation, and lack of capital.